Магазини роздрібної торгівлі як елемент громадського простору приміських поселень - Крушельницький, Р. О.; Krushelnytskiy, R. (Видавництво Львівської політехніки, 2018)
Присвячено дослідженню розташування магазинів роздрібної торгівлі у примісь¬ких поселеннях та функціонуванню простору навколо них. На прикладі с. Зимна Вода здійснено тривалий емпіричний аналіз організації магазину та території довкола нього, соціальних відносин відвідувачів та впливу архітектури на характер поведінки і навпаки.

Nowadays, we have a situation in Ukraine, when large companies control the trade market; in this case, small companies have no chance to compete with them. Nevertheless, it should be understood that small shopes carry a very important mission in suburban settlements. In a situation when the property market demanded to sell any free territory for housing development, we got a situation with a deficit of “third places” located close to our houses where we can walk. In a situation when we do major purchases in supermarkets or shopping centres, we lose places where people could meet, talk or manage some small issues or ask for advice. It is important to understand that the problem of finding communication is most acute for older people who do not have enough money to visit expensive entertainment establishments, in this situation “third places” as shops, pharmacies, bazaars, etc. become a place where one can meet someone, and spend some time in a good company. In situation when the shop is close to their houses they don’t use thei own cars or public transport so it doesn’t load transport system. These third places work as a forum for discussion and exchange of views, give the opportunity to share and discuss the latest news, in such circumstances they become a real public space. Also, in such places we can often see working meetings of people who do not have their own office. Therefore, the article is devoted to the study of the location of small shops in the structure of suburban settlements, the distances between them and the basic principles of choosing location. For research was chosen Zymna Voda village and conducted a long-term empirical analysis of the organization of the store and the surrounding area, the social relations of visitors and the influence of architecture on the behavior. The article analyzed the shop, the stages of its development and the functioning of the space around it. A brief comparative analysis with a neighboring object was also carried out and at the end of the article the main conclusions were drawn regarding the organization and functioning of the space. They do not require significant costs and the use of the car does not load the transport system
Retail shops as an element of the public space of suburban settlements
Keywords: громадський простір; торговельні заклади; магазин; public space; shopping objects; shop; 725.21; 72.06